2022
DOI: 10.3390/healthcare10071224
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Internet-Based Cognitive Behavioral Therapy for Depression and Anxiety among Global Population during the COVID-19 Pandemic: A Systematic Review and Meta-Analysis of a Randomized Controlled Trial Study

Abstract: Background: Depression and anxiety have become the most common mental health disorders worldwide during the COVID-19 pandemic, and increasing interest in telemedicine has led to the innovation of using internet-based cognitive behavioral therapy (iCBT). Objective: This systematic review and meta-analysis aimed to evaluate the efficacy of iCBT for depression and anxiety among the global population during the COVID-19 pandemic. Methods: A literature search was conducted on PubMed, Scopus, Cochrane, ProQuest, Wil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 63 publications
(93 reference statements)
1
12
0
2
Order By: Relevance
“…However, they have indicated that the available literature highlights the problem of availability of IT equipment and internet access to include support for broader target groups [ 24 ]. Similar findings were reported by Komariah et al [ 40 ]. A systematic review along with a meta-analysis assessed the effectiveness of iCBT in treating depression (6778 patients) and anxiety (6556 patients) among global populations.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, they have indicated that the available literature highlights the problem of availability of IT equipment and internet access to include support for broader target groups [ 24 ]. Similar findings were reported by Komariah et al [ 40 ]. A systematic review along with a meta-analysis assessed the effectiveness of iCBT in treating depression (6778 patients) and anxiety (6556 patients) among global populations.…”
Section: Discussionsupporting
confidence: 92%
“…Adherence to remote programmes has previously been shown to be at a high level. On the other hand, it has been shown that clinician-guided delivery is more acceptable than self-guided intervention [ 40 , 41 ]. Recent systematic reviews have shown that videoconferencing interventions delivered by health care professionals are effective in improving anxiety and depression in adults when delivered live and one-on-one [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, online psychotherapies may be essential for improving mental health issues in the context of COVID-19, such as cell phone interventions. In the literature, some online psychotherapies have been used such as mobile phone interventions (mHealth apps) (Tran et al, 2018 ), Internet-Based Cognitive Behavioral Therapy (Komariah et al, 2022 ); digital cognitive behavioural therapy (Soh et al, 2020 ). Online psychotherapies may be feasible and have great promise in reducing mental health problems in adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…Para minorar os efeitos deletérios da ausência de atendimento psicoterapêutico, sobretudo num período com aumento agudo de ansiedade (KOMARIAH et al, 2022) e depressão (KUBON et al, 2021), como é uma pandemia, houve rápido desenvolvimento do atendimento à distância, a chamada telessaúde. Tanto por parte dos profissionais médicos, quanto por parte dos profissionais da psicologia.…”
Section: Discussionunclassified